A Simplified Method of Flexible Conductors Mechanic Calculation in Switchgears without Restrictions on the Number of Taps - Yu. V. Bladyko; E. G. Ponomarenko; P. I. Klimkovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of the mechanical calculation of flexible conductors of switchgears and power lines is to determine the sag, tensions, and loads on support structures, minimum distances to adjacent live parts and some other parameters. Calculations should be made taking into account distributed and concentrated loads. Distributed loads directed vertically are determined by the weight of the wire, insulator strings, and possible ice deposits on them. Distributed loads in the horizontal plane should be calculated in climatic conditions with lateral wind pressure. Concentrated loads are created by such elements as taps to electrical devices, phase-to-phase insulating spacers, barrier balls, loops, etc. Concentrated loads mainly act in the vertical plane, and in the case of taps, they can have an almost arbitrary spatial direction. The most accurate methods of mechanical calculation of flexible conductors include methods based on the numerical solution of the equation of wires in the form of a flexible elastic thread. Such an algorithm is implemented in the author's computer program MR21. However, in many cases, simplified methods of mechanical calculation are preferable, as they are available to a wider range of users. The simplified method of mechanical calculation of flexible conductors proposed in the article is based on the equation of state of the wire and allows taking into account concentrated and distributed loads. Various climatic regimes and loads are taken into account using the horizontal and vertical load factors in the calculated and initial modes. Expressions are proposed for calculating the above coefficients for any number of taps in a span and with an accurate approach to taking into account their spatial arrangement. Formulas for calculating sag and horizontal deflections of conductors are given, too. The MR21 computer program, tested earlier, has been used in this work as a tool for checking the calculation results using the proposed simplified method.